Making dry forests work for the poor in Africa - building on success - Center for International Forestry Research (Center for International Forestry Research, 2004)
Eradicating poverty is arguably the greatest global challenge facing the world today and is a necessary precondition for sustainable development. To reach the poverty-reduction goals, bold action is required. In this Livelihood Brief we highlight some success stories, showing how sustainable management of forest resources has led to positive livelihood impacts. Four main lessons can be learned from these. Forest products can enhance peoples' livelihoods, but creating value requires changing the form or location of the products or the timing of their delivery to markets. Entrepreneurship is important. The people who succeeded had the confidence to seize the initiative when opportunities arose. Organisation matters; where people can organise themselves they benefit from opportunities to exchange information, learn from each other's experiences, share resources, and undertake joint activities. They have more voice. External assistance can make a difference, by helping people improve the quality of their products, gain access to technology and markets, or overcome other barriers to entry.